The influence of religiosity and tax awareness on tax compliance: Case study: Pondok Pesantren Daarussalam Depok - Sugiarti, Rita; Akbar, Lutfia Rizkyatul; Alianny, Alin (Educoretax, 2025)
Tax compliance of citizen becoming important since it influences tax revenue of a country.  Moreover, In Indonesia more than 70% of state revenue comes from tax. This study aims to examine the influence of religiosity and tax awareness on tax compliance. The Theory of Planned Behaviour and Social Learning Theory are used as the foundational theories in the analysis. The population is all teachers at Pondok Pesantren Daarussalam Depok. Samples are selected using Saturated Sampling. The number of samples were 57 respondents, consisted of 39 male teachers and 18 female teachers which represent 81% of teacher population (in total 70 teachers) in Pondok Pesantren Darussalam. This study used quantitative approach with primary data from quiestionaires distribution. Data analysis was conducted using analysis of multiple regression. The result indicate that religiosity does not effects on tax compliance, while tax awareness has positive influence. The findings in this study imply the importance of tax awareness, as Indonesia adopt a self-asessment system, where citizen’s tax compliance is greatly influenced by their tax awareness.